PEMURNIAN ENZIM SEFALOSPORIN-C ASILASE DAN OPTIMASI PROSES KROMATOGRAFI PENUKAR ION - Nasution, Uli Julia; Wijaya, Silvia Melinda; Wibisana, Ahmad; Safarrida, Anna; Rachmawati, Indra; Puspitasari, Dian Japany; Naim, Sidrotun; Mahsunah, Anis Herliyanti; Wulyoadi, Sasmito; Suyanto, Suyanto (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
Purification of Cephalosporin-C Acylase and Its Optimization of Ion-Exchange ChromatographyABSTRACTCephalosporin-C acylase (CCA) has an important role in the one-step conversion of cephalosporin-C into 7-ACA. Purification process aims to increase specific activity of CCA enzyme. Purification began with cell lysis, ammonium sulphate precipitation, dialysis, ion exchange chromatography (IEC) and size exclusion chromatography. IEC optimization of elution step was also done to compare gradient and isocratic elusion. Purification was capable to increase the enzyme purity upto 33.66 fold, with specific activity of 3.00 U/mg and the yield reached 41.41%. Optimization of elusion during IEC showed that isocratic protein elusion was more efficient (taking shorter time, 3 column volume (CV) only) than that of gradient batch (up to 9 CV). SDS-PAGE analysis demonstrated that the recombinant CCA enzyme existed in two types, active enzyme containing α-subunit (25 kDa) and β-subunit (58 kDa), and inactive enzyme (83 kDa) as precursor. Furthermore, 30% ammonium sulphate saturated precipitation was able to precipitate this inactive CCA.Keywords: 7-ACA,CCA, cephalosporin C, protein purification, specific activity ABSTRAKSefalosporin-C asilase (CCA) merupakan enzim yang berperan penting dalam konversi satu tahap sefalosporin-C menjadi 7-ACA. Proses purifikasi merupakan salah satu cara untuk meningkatkan aktivitas spesifik enzim CCA. Proses purifikasi dimulai dari memecah sel, diikuti dengan tahap presipitasi menggunakan amonium sulfat, dialisis, kromatografi penukar ion (IEC) dan kromatografi eksklusi. Optimasi proses IEC pada tahap elusi juga dilakukan untuk membandingkan elusi enzim CCA secara gradien dan isokratik. Proses purifikasi pada penelitian ini mampu meningkatkan kemurnian enzim hingga 33,66 kali, dengan aktivitas spesifik sebesar 3,00 U/mg dan perolehan enzim sebesar 41,41%. Hasil optimasi IEC pada proses elusi secara isokratik lebih efisien dari segi waktu (hanya membutuhkan 3 kolom volume (CV) dibandingkan dengan secara gradien (sampai 9 CV). Hasil SDS-PAGE menunjukkan bahwa CCA rekombinan merupakan enzim dengan 2 macam bentuk yaitu enzim aktif, yang terdiri dari subunit α (25 kDa) dan β (58 kDa), dan enzim tidak aktif berupa prekursor (83 kDa). Proses presipitasi menggunakan amonium sulfat 30% tersaturasi dapat mengendapkan prekursor CCA.Kata Kunci: 7-ACA, aktivitas spesifik, CCA, purifikasi protein, sefalosporin C